Accessory lateral discoid meniscus - (:unkn) unknown (SPRINGER, 2006)
The lateral meniscus tends to have more developmental variation than the medial counterpart. This is a report of an accessory discoid layer of lateral meniscus. All arthroscopic, magnetic resonance imaging and histopathological views are presented.
Keywords: accessory discoid; meniscus; double-layered; KNEE-JOINT